Preventing Sexual Harassment in Higher Education: A Framework for Prevention Science Program Development. - Crusto, Cindy A.; Hooper, Lisa M.; Arora, Ishita S. (Journal of Prevention, 2024)
Sexual harassment is an intractable problem that harms the students, community, culture, and success of institutes of higher education (IHEs). The alarming prevalence of sexual harassment at IHEs highlights the urgent need for effective prevention programs. However, there are few empirically supported preventive interventions that effectively target the factors that most impact the determinants, trajectory, and short- and intermediate-term effects of sexual harassment. In this paper, we overview the problem of sexual harassment and propose an organizing framework to help IHEs develop effective interventions to prevent sexual harassment. Guided by prevention science, we propose a framework—modified from SAMHSA's (2019) guidelines for prevention practitioners—that underscores the criticality of trauma- and equity-informed characteristics in prevention programs. We offer a discussion on how IHEs must consider and evaluate the empirical evidence of effectiveness, flexibility, cultural competency, and sustainability when developing and adapting prevention programs to reduce and—ultimately—ameliorate sexual harassment. We conclude with recommendations that can provide a roadmap for higher education stakeholders and researchers to prevent this urgent public health concern.